Experimental investigation of the mechanism of supercritical CO2 interaction with tight sandstone - Peng, Huan; Yang, Jian; Peng, Junliang; Pu, Junhong; Liu, Qiang; Su, Jun; Liu, Jin (Frontiers in Energy Research, 2022)
One of the important technologies for combating global climate change is CCUS (Carbon Capture, Utilization, and Storage), which aims to address the issue of “greenhouse effect” generated by a significant amount of greenhouse gas emissions. Supercritical CO2, a new type of anhydrous fracturing fluid with broad application prospects in low-pressure tight sandstone gas reservoirs, has several advantages over traditional water-based fracturing fluids, including quick flowback, minimal damage to the reservoir, and the ability to realize in-situ storage of greenhouse gases. The tight sandstone cores from the Jinqiu Gas field in the Sichuan Basin were used in an experimental investigation on the interaction mechanism between supercritical CO2 and tight sandstone to examine the viability of supercritical CO2 fracturing with tight sandstone, and analysis of the samples’ post-reaction samples’ mineral composition, microstructure, mass change, and total salinity change. The interaction of tight sandstone with supercritical CO2 results in an increase in quartz content, a decrease in clay mineral content, the formation of new minerals, and partial mineral dissolution on the surface of the sample. Since the degree of mineral dissolution of sandstone samples increases with time, CO2 can be stored in tight sandstone as carbonate minerals. This study evaluates how supercritical CO2 interacts with tight sandstone and can offer a solid theoretical foundation and experimental evidence in favor of CO2in-situ storage in tight sandstone gas reservoir.